Validade e confiabilidade das medidas de confiança interpessoal : o barômetro das Américas - Rennó Junior, Lucio Remuzat (2011)
Using an innovative databank, this article conducts validity and reliability tests for various measures of the concept of interpersonal trust. The Brazilian round of the Americas Barometer 2008 included different measures of the interpersonal trust concept, allowing the evaluation of its internal consistency and external validity. After a battery of tests, the conclusion is that the measure of interpersonal trust traditionally used in series like the World Values Survey, Eurobarometer, and Latinobarometer suffers from serious validity and reliability problems.